Stability of stochastic systems in the diffusion-approximation scheme - Korolyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using a solution of a singular perturbation problem, we obtain sufficient conditions for the stability of a dynamical system with rapid Markov switchings under the condition of exponential stability of the averaged diffusion process.